2019
DOI: 10.1039/c8cp07292b
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Norrish type I and type II reactions: an ab initio mechanistic study highlighting singlet-state mediated chemistry

Abstract: Norrish reactions are important photo-induced reactions in mainstream organic chemistry and are implicated in many industrially and biologically relevant processes and in the processing of carbonyl molecules in the atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 65 publications
0
37
0
Order By: Relevance
“…By comparing our gaseous spectra with the solution‐phase absorption spectrum, we conclude that the non‐statistical odd‐electron photofragments (pathways (2a) and (2c)) are the direct photodegradation products of the T 1 state. Indeed, the long‐range repulsive interaction inherent in the triplet state is known to aid in the breakdown of such states into such free radical pairs . The identification of the direct photoproducts in this work is important as it can guide detection of the direct photolysis products in future condensed‐phase studies, as well as informing assessment of the possible toxicity of photoproducts.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing our gaseous spectra with the solution‐phase absorption spectrum, we conclude that the non‐statistical odd‐electron photofragments (pathways (2a) and (2c)) are the direct photodegradation products of the T 1 state. Indeed, the long‐range repulsive interaction inherent in the triplet state is known to aid in the breakdown of such states into such free radical pairs . The identification of the direct photoproducts in this work is important as it can guide detection of the direct photolysis products in future condensed‐phase studies, as well as informing assessment of the possible toxicity of photoproducts.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of cyclobutanone, one product of this photochemistry is a ketenecontaining compound most likely formed via internal conversion to S 0 through an S 1 /S 0 conical intersection (Fig. 1), 51 but other direct photoproducts of this and the other cyclic ketones were not identied.…”
Section: Mechanistic Interpretation Of Teas and Tvas Measurementsmentioning
confidence: 99%
“…Norrish type I reactions have traditionally been assumed to start with efficient S 1 → T 1 ISC Bamford, 1936, 1937;Diau et al, 2001Diau et al, , 2002, and indeed, reference to Figure 2A suggests that S 1 → T 1 ISC in CPE could constitute another route to the ring-opened species. However, the recent literature includes a growing number of predictions and/or demonstrations of purely singlet-state enabled fission of the C-C bond in the α-position (relative to the carbonyl group) (Maeda et al, 2010;Nádasdi et al, 2010;Marchetti et al, 2019), notably in strained cyclic ketones like cyclobutanone (Xia et al, 2015;Shemesh et al, 2016;Kao et al, 2020). In all such cases investigated to date, the C-C=O moiety remaining after photochemical cleavage of the other α-C-C bond is predicted to be near linear at the CI (Marchetti et al, 2019)-as is found in the present case also (see Figure 2).…”
Section: Reaction Path Following Photoexcitationmentioning
confidence: 99%